Effective media communication of disasters: Pressing problems and recommendations - Ginter Peter M; Robinson Jennifer A; Gower Karla K; Evans William; Lowrey Wilson; McCormick Lisa C; Abdolrasulnia Maziar (BMC, 2007)
Abstract Background Public health officials and journalists play a crucial role in disseminating information regarding natural disasters, terrorism and other human-initiated disasters. However, research suggests that journalists are unprepared to cover terrorism and many types of natural disasters, in part because of lack sufficient expertise in science and medicine and training. The objective of this research was to identify solutions to problems facing journalists and public health public information officer (PIOs) of communicating with the public during natural and human-initiated disasters. Methods To assist in identifying the most pressing problems regarding media response to health-related risks such as terrorism and large-scale natural disasters, 26 expert advisors were convened, including leaders representing journalists and public information officers, state health officials, experts in terrorism and emergency preparedness, and experts in health, risk, and science communication. The advisory group participated in pre-arranged interviews and were asked to identify and review bioterrorism educational resources provided to journalist. All advisory group members were then invited to attend a day long meeting January 29, 2004 to review the findings and reach consensus. Results The most pressing problems were found to be a lack of coordination between PIO's and journalists, lack of resources for appropriately evaluating information and disseminating it efficiently, and a difference in perception of PIO's and journalist towards each others role during emergency situations. The advisory board developed a list of 15 recommendations that may enhance communication plans betweens PIO's, journalist and the public. The solutions were meant to be feasible in terms of costs and practical in terms of the professional and organizational realities in which journalists and PIO's work. Conclusion It is clear that PIO's and journalists play crucial roles in shaping public response to terrorism and other disasters. The findings from this formative research suggest that perspectives and organizational processes often limit effective communication between these groups; though practical solutions such as participation of journalists in drills, scenario exercises, sharing of informational resources, and raising awareness at professional trade meetings may enhance the timely dissemination of accurate and appropriate information.